Sweet Sugar Managed with Sweet Pills - Aphale, Parth (Homœopathic Links, 2017)
A case is presented that shows that homeopathy can be used effectively in the treatment of diabetes.
Keywords: Lycopodium clavatum; Insulin; Replacement therapy